Point-of-use Ultrafast Single-step Detection of Food Contaminants: A Novel Microfluidic Fluorescence-based Immunoassay with Integrated Photodetection. (2016) - Soares, R.R.G.; Santos, D.R.; Pinto, I.F.; Azevedo, A.M.; Chu, V.; Aires-Barros, M.R.; Conde, J.P.
Abstract: The assurance of strict food safety standards is a major challenge in modern society. Mycotoxins, in particular, are produced by fungi during production, storage or transport, posing serious health concerns to humans and animals. Aiming at developing a point-of-use tool for the rapid detection of mycotoxins at the required regulatory levels, we report a microfluidic ultrafast and single-step fluorescence-based immunoassay, using minimal amounts of reagents. This assay was integrated with 200×200 μm thin-film a-Si:H photodiodes towards a compact detection system. Aflatoxin B1 was detected at 1 ng/mL after 2 min assay time, among the fastest reported in the literature.